The Effect Of Organizational Culture And Work Stress On Employee Performance At The Grand Inna Medan Hotel - Tambunan, Maudy Istiningdiah; Eriza, Faisal; Siregar, Onan Marakali (Cattleya Darmaya Fortuna, 2023)
Performance is a work achieved by a person in carrying out the tasks assigned to him on the basis of experience and ability and the time given. Therefore, in carrying out a job, a good organizational culture and minimal stress level are needed so that it can encourage employees to improve their performance. This study aims to determine the effect of organizational culture and work stress on employee performance at the Grand Inna Medan hotel. The influence of organizational culture and work stress will be analyzed partially and simultaneously on employee performance. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out by non-probability samples with the saturated sample method and using 50 respondents as samples. The primary data used in this study was obtained by distributing questionnaires directly to employees, while the secondary data was obtained through a literature study. The data analysis method used is validity test, reliability test, classical assumption test, multiple regression test, and hypothesis testing. The results of this study indicate that organizational culture and work stress have a positive and significant effect either partially or jointly on employee performance at the Grand Inna Medan hotel by 14.4%. It means that organizational culture and work stress owned by employees are sufficient to explain employee performance. The better the organizational culture and the lower the level of stress experienced, the more employee performance will increase.